Essentials of Pediatric Cataract Surgery - Khokhar, Sudarshan Kumar; Dhull, Chirakshi; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
The book highlights various pediatric cataract surgeries. It covers variants of pediatric cataract along with other rare morphologies. It covers selected challenging clinical situations along with surgical management steps. Additionally, it includes the management of surgical complications. The book provides relevant concise text supported by clinical pictures and 50 short videos. This book is a collection of clinical images and videos over 2 decades. Chapters cover recent advances in the field of pediatric cataract, such as ultrasound biomicroscopy, intraoperative rhexis assistant, operative room aberrometry. The accompanying video describes the surgical procedures with a voiceover lucidly explaining every step. It discusses unique cases of buphthalmous with cataract, anterior segment dysgenesis, persistent fetal vasculature and pre-existing persistent capsular defect with their latest management techniques. This book is relevant for practicing ophthalmologists and students alike.
Part I: Management of pediatric cataract -- Pre-operative evaluation and investigative modalities in pediatric cataract -- Anesthesia considerations -- IOL power calculation -- Step wise surgical treatment of pediatric cataract -- Bag in the lens -- Secondary IOL in congenital cataract -- Intra-operative and post-operative complications -- Visual axis opacification management -- Post-operative management -- Part II: Pediatric cataract surgery in challenging situations -- Surgery in different scenario - big eyes and small eyes, plaques - anterior and posterior -- Persistent fetal vasculature -- Pre-existing posterior capsular defect -- Management of subluxated lens and spherophakia -- Traumatic cataract -- Uveitic and complicated cataract -- Infective cataract (TORCH) -- Anterior segment dysgenesis including aniridia -- Cataract associated with ROP, retinal pathologies and miscellaneous cataract (drug induced, radiation induced, albinism).
Keywords: Ophthalmology; Ophthalmology; Cataract; Cataract Extraction; Child